If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -15 = 4y + 12 Reorder the terms: -15 + -5y = 4y + 12 Reorder the terms: -15 + -5y = 12 + 4y Solving -15 + -5y = 12 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -15 + -5y + -4y = 12 + 4y + -4y Combine like terms: -5y + -4y = -9y -15 + -9y = 12 + 4y + -4y Combine like terms: 4y + -4y = 0 -15 + -9y = 12 + 0 -15 + -9y = 12 Add '15' to each side of the equation. -15 + 15 + -9y = 12 + 15 Combine like terms: -15 + 15 = 0 0 + -9y = 12 + 15 -9y = 12 + 15 Combine like terms: 12 + 15 = 27 -9y = 27 Divide each side by '-9'. y = -3 Simplifying y = -3
| 8*y^2-72=0 | | 20(37x+20x)=7.06 | | 1.6=p/7 | | -5(9+X)= | | 2x^2+5x-10=y | | ln(8)-ln(2)= | | X^2+52x+100=0 | | 11xsquared-9x=0 | | (7-2)(5-8)= | | 3(4x-12)=12(x+3) | | (8X^2-2X+7)-(2X^2-4X-7)=0 | | 45+15y=y | | 2x+26y=3x+21y | | 9y^2-49r^2=0 | | 0=(5x-31)(x)-75 | | -2.8y=3.08 | | 10+25x=5(5x+3) | | 3128=34.08x | | ln(x-5)=lnx-ln*5 | | 24x+6= | | 3128=34.8x | | k+1=18 | | 5x+25=99 | | p(x)=-x^2+34x+29 | | 2x-13=-3x-3 | | 3x^3-75x^3= | | 4(6t+1)-16=t-(t+11) | | 37d^2-40d=0 | | 3x-14+x=x-23 | | (y-3)-(y-5)-7= | | -6r+2(r+2)=-20 | | 3x^3-75x^3=0 |